Prospects of Indonesian Rice Self-sufficiency As a Food Security Effort Using a Dynamic System Model - Mubarokah, Syaima Lailatul; Miftah, Himmatul (Universitas Djuanda, 2023)
Problems at the level of rice production faced include reduced agricultural land due to land conversion, damage to irrigation networks, pests and diseases in production and not yet maximizing productivity because the use of seeds and fertilizers has not been optimal. Meanwhile, at the consumer level, the need for rice continues to increase, both to meet industrial needs, to meet household (RT) and non-RT needs. The purpose of this research is to simulate a scenario of achieving self-sufficiency in rice in the dynamic system model, to find out the key factors that determine the achievement of self-sufficiency in rice in Indonesia and to develop policy recommendations needed to achieve self-sufficiency in rice towards food security. The research method used is a system dynamic approach using secondary data to build a simulation model. The simulation results show that the paddy field printing program contributes the most to increasing rice self-sufficiency. Furthermore, the intensification and reduction of rice consumption, but these two policies did not have a major impact on self-sufficiency in rice, in contrast to the results of achieving self-sufficiency in the extensification program. But unfortunately, creating paddy fields, intensification in the form of using certified seeds and decreasing consumption are the biggest obstacles currently facing agricultural development.